2011
DOI: 10.1186/1756-3305-4-113
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-treated net (ITN) ownership, usage, and malaria transmission in the highlands of western Kenya

Abstract: BackgroundInsecticide-treated bed nets (ITNs) are known to be highly effective in reducing malaria morbidity and mortality. However, usage varies among households, and such variations in actual usage may seriously limit the potential impact of nets and cause spatial heterogeneity on malaria transmission. This study examined ITN ownership and underlying factors for among-household variation in use, and malaria transmission in two highland regions of western Kenya.MethodsCross-sectional surveys were conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
185
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(219 citation statements)
references
References 37 publications
25
185
9
Order By: Relevance
“…Recent studies in Kenya and Tanzania also identified strong seasonality to LLIN use. 25,30,38 This seasonality in use may be related to temperature (LLINs are often described as uncomfortable to sleep under when it is hot) and mosquito density in households (LLIN use is higher when mosquitoes are present). Previous studies in Zanzibar, Kenya, and Ghana found the presence of culicine mosquitoes to be associated with LLIN use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in Kenya and Tanzania also identified strong seasonality to LLIN use. 25,30,38 This seasonality in use may be related to temperature (LLINs are often described as uncomfortable to sleep under when it is hot) and mosquito density in households (LLIN use is higher when mosquitoes are present). Previous studies in Zanzibar, Kenya, and Ghana found the presence of culicine mosquitoes to be associated with LLIN use.…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, children aged 5-14 years reported significantly lower LLIN use. 38 School-based LLIN distributions and educational campaigns may help target this high-risk age group, especially if coupled with educational campaigns. Traditionally, LLINs are targeted to children younger than 5 years and pregnant women, often excluding older children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results reveal that Granger causality run from ITNs to under-five malaria mortality. ITNs protect individuals from mosquito nuisance, suppress the vector population and reduce their ability to transmit malaria and are highly effective in reducing malaria morbidity and mortality (Atieli et al, 2011). However, the insignificant correlation association between ITNs and under-five malaria mortality might be due to usage of ITNs from one household member to other household member which can limit the potential impact of nets (Atieli et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The mass distribution is reflected in more houses reporting having enough LLINs to cover every sleeping space at end line. Studies have reported mass distribution campaigns, especially when coupled with an awareness campaign of the benefits of using LLINs, as improving LLIN usage (Atieli, Zhou et al 2011;Zhou, Li et al 2014). While this positive improvement supports efforts towards malaria control, sustaining the changes may require a longer and persistent effort with educational programmes and cues to action.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria awareness-raising, advocacy, case management, and prevention efforts have reaped the benefits of social science research and as a result, many programmes are implemented and evaluated in a more effective manner (Mwenesi 2005). Such studies have been conducted about: malaria treatment strategies (Snow, Peshu et al 1992;Mwenesi, Harpham et al 1995;Ruebush, Kern et al 1995;Marsh, Mutemi et al 2004;Zurovac, Rowe et al 2004;Abuya, Mutemi et al 2007); LLINs availability, acceptability, affordability and determinants of utilisation at household and community levels ; Alaii, Dye, Apondi et al 2010;Githinji, Herbst et al 2010;Hightower, Kiptui et al 2010;Atieli, Zhou et al 2011;Mutuku, Khambira et al 2013); and the economic cost of malaria (Meltzer, Terlouw et al 2003;Chuma, Thiede et al 2006). …”
mentioning
confidence: 99%